Agronomic evaluation of forage grasses under grazing - Botrel, Milton de A.; Alvim, Maurílio José; Mozzer, Otto Luiz (Pesquisa Agropecuaria Brasileira, 2014)
An experiment designed to evaluate agronomically 25 forage grasses under grazing was conducted at the Centro Nacional de Pesquisa de Gado de Leite (CNPGL-EMBRAPA). The soil was a low fertility oxisol, in a hilly country characteristic of a large area of South-east Brazil). The species Brachiaria decumbens, B. brizantha and Setaria sphacelata presented high growth rates as well as good soil cover. The species Panicum maximum cv. Makueni and Andropogon gayanus cv. Panaltina though included amongst the highest yielding grasses, failed to offer a good soil cover. Forage acceptability by grazing animals was high for A. gayanus, P. maximum cv. Makueni and S. sphacelata, low for B. humidicola and B. dictyoneura and intermediate for the other species. Crude protein content in the dry matter was eather high in the majority of the grasses, but varied among species and seasons.